The cytochrome P450 inhibitor, ketoconazole, inhibits oxidized linoleic acid metabolite-mediated peripheral inflammatory pain - Ruparel Shivani; Green Dustin; Chen Paul; Hargreaves Kenneth M (SAGE Publishing, 2012)
Abstract Background Oxidized linoleic acid metabolites (OLAMs) are a class of endogenous agonists to the transient receptor potential V1 (TRPV1) receptor. Although TRPV1 mediates inflammatory heat hyperalgesia, it is not known if the OLAMs contribute to the peripheral activation of this receptor during tissue inflammation. In the present study, we evaluated whether the OLAM system is activated during inflammation and whether cytochrome P450 enzymes mediate OLAM contributions to heat hyperalgesia using the complete Freund's adjuvant (CFA) model of inflammation. Results Our results demonstrate that the intraplantar (ipl) injection of anti-OLAM antibodies significantly reversed CFA-induced heat hyperalgesia. Moreover, application of lipid extracts from inflamed rat skin to cultured sensory neurons triggered a significant release of iCGRP that is blocked by co-treatment with I-RTX, a TRPV1 antagonist. To determine the role of CYP enzymes in mediating OLAM effects, we used a broad spectrum CYP inhibitor, ketoconazole. Pretreatment with ketoconazole inhibited the release of TRPV1 agonists in lipid extracts from inflamed skin and significantly reversed CFA-induced heat hyperalgesia by a peripheral mechanism of action. Moreover, the ipl injection of linoleic acid to rats 24 hr after CFA evoked spontaneous nocifensive behaviors that were significantly reduced by capsazepine, by knockout of the TRPV1 gene, or by pretreatment with either anti-OLAM antibodies or ketoconazole. Conclusions Taken together, our data suggests that OLAMs contribute to inflammatory nociception in the periphery and that cytochrome P450 enzymes play a crucial role in mediating OLAM contributions to inflammatory heat hyperalgesia.